Infections related to health care in nurses' education - Suellen Karina de Oliveira Giroti; Mara Lucia Garanhani (Universidade Federal do Ceará, 2015)
Objective: to analyze the introduction of the theme infections associated to health care in nurses' education. Methods: this is a qualitative study, with documentary analysis of 16 interdisciplinary modules of a nursing integrated curriculum from a State University in Paraná, conducted in 2013. Results: in the first year of the course there were no references to infections. From the second to the fourth years there were 44 entries that approached: hand washing, actions to prevent infections in newborns, children, adults, pregnant women and surgical patients in different health environments, biosecurity, Regulatory Standard n. 32, dental-medical-hospital supplies processing, among others. One highlighted strengths and flaws on the approach of this theme in many moments of an integrated curriculum. Conclusion: the infections associated to health care, given their relevance and complexity, should be introduced in a transversal and continuous way in nurse's education, providing nursing students with a reflexive and critical learning.